INTRODUCTION OF THE SYMBOL OF THE SCOUTING MOVEMENT DURING SCOUTING EDUCATION ORENTATION - Nasywa Salsabila; Auliah Fitriani; Mutiara Khairani (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques carried out in this research are as follows: (1) Observation (Observation documentation and traiangulation. Results of research on the orientation process in Scout education by and for oneself with the help of each member, so that its practice can be carried out on one's own initiative, full of awareness, independence, concern, responsibility and moral attachment, both as an individual and as a member